Evaluación de la Calidad de Aire en el Proyecto de Explotación Cantera Camucha, distrito de Morococha, provincia de Yauli, Junín - Licla Tomayro, Luis Ricardo (2021)
The objective of this research was to evaluate the air quality in the Camucha Quarry Exploitation Project, located in the Morococha district, Yauli province, Junín region. For this, the gravimetric method established in the National Protocol for the Monitoring of Environmental Air Quality (MINAM, 2017) was used, for the purpose of determining the concentration of particulate material (PM10 and PM2.5) to windward and leeward of the area of exploitation. The results show that the levels of particulate matter comply with the maximum values allowed in the Environmental Quality Standards (ECA) for Air, which indicates that air quality does not represent a risk to worker’s health or the environment.